THE ROLE OF CLASSROOM MANAGEMENT IN CREATING AN EFFECTIVE ENGLISH LEARNING - Evajustika Gultom; Saunir Saun (Journal of English Language Teaching, 2016)
In this paper, the writer discusses about classroom management that is done by a teacher. Classroom management is the ability of a teacher to organize, nurture, and manage the learning environment and the talents of its students  become better, focused, and organized so that time can be used efficiently. The objective of classroom management is to provide facilities for a variety of learning activities of students in the social, emotional, and intellectual in the classroom. In the management class, the most important is the role of manager of the class or the teacher. Teachers play a role in selecting the most effective learning strategies and also design the class curriculum. Implementation of an effective role of the teacher will create a learning environment that is more convenient, interactive and active and effective. This paper is expected to provide new insights to teachers and educators about the role of classroom management can create an effective English learning. The teacher should implemented the classroom management effectively so can create an effective English learning.